Higher Education System of Inner Mongolia Autonomous Region (People’s Republic of China) in 1950s-1960s - I. G. Aktamov; . Daiqin (Научный диалог, 2023)
This study analyzes the establishment and development of higher education in the first autonomous region within the People’s Republic of China (PRC). After the establishment of the Inner Mongolia Autonomous Region (IMAR) in 1947, the regional leadership made efforts to develop the education sector. Improving literacy rates was a strategic goal for the development of the region and the entire country. The preparation of highly qualified personnel was also crucial for the accelerated development of the state. The novelty of this study lies in the utilization of original sources on the history of education in the PRC during its initial stages of construction. The author concludes that the establishment of the first higher education institution, the Pedagogical Institute of IMAR, met the needs of the region and stimulated the development of the entire educational system. In the early years of educational development in IMAR, special attention was given to the study of the Mongolian language and script, as well as the bilingual implementation of educational programs. This was necessary for the development of intercultural interaction and ideological consolidation among the population of IMAR.